A new variant of ARFIMA1 Process and its predictive ability - Yip, Chee Yin; Quah, Soon Hoe (Canadian Center of Science and Education, 2008)
ARFIMA models generated an enormous amount of interest in the literature about three decades ago.However, this interest vaned after Granger (1999) showed that an ARFIMA process might have stochastic properties that do not mimic the properties of the data at all.The empirical results of our research in which we used exchange rate data for the analysis, show that a variant of an ARFIMA process indeed can beat the ARFIMA, the Random Walk and the ARMA process of the order one in out of sample forecasting.This indirectly indicates that our variant of the ARFIMA process can be considered as the data generating process for the long memory time series.